First application of a droplet digital PCR to detect Toxoplasma gondii in mussels - Mancusi, Andrea; Proroga, Yolande T. R.; Giordano, Angela; Girardi, Santa; D’Orilia, Francescantonio; Pinto, Renato; Sarnelli, Paolo; Rinaldi, Laura; Capuano, Federico; Maurelli, Maria Paola (Frontiers in Microbiology, 2023)
Toxoplasmosis, caused by the protozoan Toxoplasma gondii, is one of the main food-, water-and soilborne zoonotic disease worldwide. Over the past 20 years many papers were published on the transmission of T. gondii by marine animals, including mollusks, which can concentrate the oocysts and release them. Sporulated oocysts may remain viable and infective for 18 months in seawater. Therefore, raw or undercooked bivalve mollusks pose a risk to humans. This study aimed to apply and validate for the first time a very sensitive digital droplet polymerase chain reaction (ddPCR) protocol to detect and quantify T. gondii DNA in mussels. Four concentration levels: 8000 genomic copies (gc)/µl, 800 gc/µl, 80 gc/µl, 8 gc/µl of a T. gondii reference DNA were tested. DNA was extracted from 80 pools of mussels (Mytilus galloprovincialis). Forty pools were contaminated with T. gondii reference DNA and used as positive controls, while 40 pools were used as negative controls. DdPCR reaction was prepared using a protocol, previously developed by the authors, for detection of T. gondii in meat. Amplification was obtained up 8 gc/µl. All infected replicates resulted positive, as well as no droplets were detected in negative controls. The droplets produced in the reaction ranged from 8,828 to 14,075 (average 12,627 droplets). The sensitivity and specificity of ddPCR were 100% (95%CI= 94.3-99.9). In addition, 100 pools of mussels collected in the Gulf of Naples were used to validate the protocol. Of these 16% were positive (95% CI= 9.7-25.0) for T. gondii. Samples were also tested by real-time PCR and no positive samples were found. Data obtained from ddPCR showed good identification of negative and positive samples with higher specificity and efficiency than real-time PCR. This tool could be very useful for a rapid sensitive detection of low DNA concentrations of T. gondii in mussels, reducing the risk of toxoplasmosis in humans.